Aalisis Standar Proses Dan Standar Penilaian Kurikulum 2013 Dalam Pembelajaran IPA Tingkat SMP Di Kabupaten Ciamis Pada Masa Pandemi Covid-19 - Supartini, Herlin; Abidin, Zaenal; Arif, Asep Ginanjar (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2022)
This study aims to analyze how the implementation of process standards and assessment standards in science learning at the junior high school level in Ciamis Regency during the Covid-19 pandemic. This research is a descriptive qualitative research using survey method. The number of subjects in this study were 4 class IX science teachers at SMPN 1 Ciamis, SMPN 1 Panjalu, SMPN 3 Panawangan and SMPN 7 Banjarsari. The sampling technique used purposive sampling type of non-probability sampling. Data collection techniques used were observation, in-depth interviews and documentation. The research instruments were observation sheets, interview guidelines and document analysis guidelines. The data analysis technique used is the Miles and Huberman Model where the qualitative data analysis process is carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the science learning process which includes the planning, implementation and assessment stages during the pandemic has generally been well implemented.